A kind of high-efficiency and environmentally friendly phosphorus-free water dispersant and preparation method thereof
By using modified copolymers and modified composite microspheres, combined with copolymerization reaction of modified lignin and sodium styrene sulfonate, the problems of low scale resistance and poor stability in the prior art are solved, and an efficient and environmentally friendly gray water dispersant is achieved, and good scale resistance and antibacterial properties are provided.
Patent Information
- Application Number
- CN202410951008.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-07-16
AI Technical Summary
In the prior art, the scale inhibition performance of various monomer scale inhibitors has low scale resistance and poor stability, and the scale inhibitors of polyphosphate groups are prone to pollute the environment, making it difficult to meet the efficient and environmental protection needs of industrial gray water treatment.
Modified copolymers and modified composite microspheres are used as main components to prepare high molecular weight modified copolymers through copolymerization of modified lignin, monomethyl fumarate and sodium styrene sulfonate, and polymer microspheres are prepared by fine emulsion method, and sodium sulfamate and dopamine are added to improve scale-resistant and antibacterial properties.
It improves the scale resistance and stability of salt scales such as Ca and Mg, and also has good antibacterial effects, avoiding environmental pollution caused by phosphate groups.
Smart Images

Figure BDA0004947238130000031 
Figure BDA0004947238130000041 
Figure BDA0004947238130000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ash water dispersants, and in particular to a high-efficiency, environment-friendly, phosphorus-free ash water dispersant and a preparation method thereof. Background Art
[0002] In order to ensure the safe and efficient operation of industrial production, water treatment has become an important guarantee for modern industrial production. The scale in gray water is divided into soft scale and hard scale. The main components of soft scale are rust, microorganisms and silt ash, and the main components of hard scale are salt scale such as carbonate, sulfate, phosphate and silicate. Due to the poor thermal conductivity of scale, serious scaling on the inner wall of boiler and heat exchange equipment will reduce the heat conduction efficiency and increase heat loss; scale will also directly cause or promote metal corrosion and shorten the service life of equipment. Therefore, selecting effective gray water dispersant to inhibit the formation of scale has positive practical significance.
[0003] Dispersants inhibit the reaction of scaling ions such as calcium and magnesium with CO3 by dissolving, chelating and dispersing in the grey water. 2- 、SO4 2- The anions form scale, thereby slowing down the scaling trend of the equipment and pipelines related to the ash water system and extending the operation cycle of the gasification device. The phosphorus-based scale inhibitors are difficult to be biodegraded due to the phosphorus and nitrogen components they contain, causing "secondary pollution" to the environment and are facing the situation of being gradually eliminated. Therefore, the research and development of efficient, phosphorus-free, green and environmentally friendly ash water dispersants has become a new development direction.
[0004] Patent application CN115477398A discloses a gray water dispersant, including acrylic acid-2-acrylamide-2-methylpropane sulfonic acid, 2-phosphoric acid-1,2,4-tricarboxylic acid butane, aminotrimethylene phosphoric acid, hydroxyethylidene diphosphonic acid and hydrolyzed polymaleic anhydride. Acrylic acid-2-acrylamide-2-methylpropane sulfonic acid has a sulfonic acid group, and aminotrimethylene phosphoric acid and hydroxyethylidene diphosphonic acid have a phosphoric acid group, so that the above monomers have the function of inhibiting calcium carbonate and calcium phosphate scale; however, organic phosphates will pollute the environment, and the various monomers used have small molecular weights. Compared with compound scale inhibitors, they have the defects of low scale inhibition rate and unstable monomer molecules. In addition, gray water in the industrial field also needs to be sterilized to prevent bacteria and viruses from growing in the water body.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide an efficient and environmentally friendly phosphorus ash-free water dispersant and a preparation method thereof, which are used to solve the technical problems that various monomer scale inhibitors in the prior art have low scale inhibition performance and poor stability, and scale inhibitors with polyphosphate groups are easy to pollute the environment.
[0007] The purpose of the present invention can be achieved by the following technical scheme: a high-efficiency and environmentally friendly phosphate-free water dispersant, which comprises, by weight, 50-60 parts of a modified copolymer, 20-30 parts of modified composite microspheres, 10 parts of hydrolyzed polymaleic anhydride, 10 parts of polyaspartic acid and 10 parts of deionized water.
[0008] Furthermore, the preparation method of the modified copolymer comprises the following steps:
[0009] A1, toluene, lignin and 3-chloropropyltriethoxysilane are mixed and stirred to obtain a mixed solid-liquid; the mixed solid-liquid is refluxed at 70-80° C. for 24 hours, and after the reaction is completed, it is naturally cooled to room temperature to obtain a reactant; the reactant is subjected to a post-treatment process to obtain chlorinated lignin;
[0010] A2, mixing chlorinated lignin and N,N-diethylallylamine, heating and refluxing for 3-5h; and then performing a post-treatment process to obtain modified lignin;
[0011] The molecular structure of lignin contains active groups such as alcoholic hydroxyl groups and phenolic hydroxyl groups. These hydroxyl groups can react with the silicon group of the coupling agent 3-chloropropyltriethoxysilane to generate chlorinated lignin. The chlorinated lignin reacts with N,N-diethylallylamine to generate ammonium lignin, which is the modified lignin prepared by the present invention. The modified lignin contains redundant carbon-carbon double bonds by grafting N,N-diethylallylamine, and can undergo multi-copolymerization reactions with other monomers to prepare a modified copolymer.
[0012] Taking coniferyl alcohol, a monomer of lignin, as an example, the reaction formula for synthesizing modified lignin is as follows:
[0013]
[0014] A3. Dissolve sodium hypophosphite, ammonium superphosphate and deionized water to obtain an initiator solution; mix and stir monomethyl fumarate, sodium styrene sulfonate and modified lignin to obtain a mixed solid-liquid; then add the initiator solution drop by drop into the mixed solid-liquid, react at 100-110° C. for 2 hours to obtain a modified copolymer.
[0015] Sodium hypophosphite and ammonium superphosphate are used to form an oxidation-reduction initiation system to obtain an initiator solution, and modified lignin, monomethyl fumarate and sodium styrene sulfonate are used as monomers to react at a specific temperature to prepare a modified copolymer.
[0016] The reaction formula for preparing the modified copolymer by copolymerization of modified lignin, monomethyl fumarate and sodium styrene sulfonate is as follows:
[0017]
[0018] Furthermore, in step A1, the dosage ratio of toluene, lignin and 3-chloropropyltriethoxysilane is 50mL:6g:10-15mL; the post-treatment process includes: centrifuging the reactants at 1000r / min for 30min and separating to obtain solid chlorinated lignin; washing the chlorinated lignin with ethyl acetate to neutrality, and then drying at 50-60°C to constant weight to obtain chlorinated lignin.
[0019] Furthermore, in step A2, the ratio of chlorinated lignin to N,N-diethylallylamine is 15-20 g:20-30 g; the post-treatment process includes: centrifuging at 1000 r / min for 15-20 min, then performing solid-liquid separation, collecting solids. The solids are washed with ethyl acetate until neutral, and then placed in an oven at 50-60° C. to dry to constant weight to obtain modified lignin.
[0020] Furthermore, in step A3, the dosage ratio of sodium hypophosphite, ammonium superphosphate and deionized water is 10g:10g:50mL; the dosage ratio of monomethyl fumarate, sodium styrene sulfonate and modified lignin is 10g:50g:10-20g.
[0021] Furthermore, the preparation method of the modified composite microspheres comprises the following steps:
[0022] B1, initiator, emulsifier and deionized water are mixed evenly, and then styrene is added, mixed and stirred to obtain a premixed solution; glycidyl methacrylate is then added dropwise to the premixed solution, and the temperature is raised to 70°C for reaction for 6-8h to obtain an emulsion system;
[0023] B2, add sodium aminosulfonate to the emulsion system, mix and stir until completely dissolved; then heat to 80-100°C for reaction for 15-20h, cool to room temperature to obtain a composite liquid; add ethanol to the composite liquid to demulsify, centrifuge to obtain a solid; wash the solid with deionized water, dry at 50-60°C to constant weight, and obtain an intermediate;
[0024] B3, tris(hydroxymethyl)aminomethane, dopamine hydrochloride and the intermediate are ultrasonically mixed to obtain a mixed solid-liquid; the mixed solid-liquid is post-treated to obtain modified composite microspheres.
[0025] Polymer microspheres are prepared from styrene and glycidyl methacrylate by a mini-emulsion polymerization method, wherein the proportion of glycidyl methacrylate in the prepared polymer microspheres is increased to obtain polymer microspheres rich in small molecule epoxy groups on the surface, and functional additives sodium aminosulfonate and dopamine hydrochloride are added when the emulsion system is not demulsified to form polymer microspheres, and the amino groups in sodium aminosulfonate and dopamine hydrochloride have high reaction activity with small molecule epoxy groups, thereby preparing modified composite microspheres polymerized with multiple functional monomers.
[0026] The reaction formula of polymer microspheres and dopamine hydrochloride is as follows:
[0027]
[0028] Furthermore, in step B1, the initiator is methyl persulfate and the emulsifier is Tween 20; the dosage ratio of the initiator, the emulsifier and the deionized water is 0.5g:5g:200mL; the mixing speed is 100r / min and the mixing time is 30-60min; the dosage ratio of styrene and glycidyl methacrylate is 10g:20-25g.
[0029] Furthermore, in step B2, the amount of sodium aminosulfonate is 15-20g, and the amount of ethanol is 10mL; the centrifugal speed is 1000r / min, and the centrifugal time is 20-30min; in step B3, the amount ratio of trishydroxymethylaminomethane, dopamine hydrochloride and intermediate is 200mL:200-300mg:200mg; the ultrasonic frequency is 20KHz, and the ultrasonic time is 10-20min; post-treatment includes: reacting the mixed solid and liquid at room temperature for 24h, and maintaining the pH value of the mixed solid and liquid at 8-9 during the reaction; centrifuging the mixed solid and liquid to obtain a solid; washing the solid with distilled water for 3-5 times, and then drying to obtain modified composite microspheres.
[0030] As another aspect of the present invention, a method for preparing a highly efficient and environmentally friendly phosphate-free water dispersant is: uniformly mixing the modified copolymer, modified composite microspheres, hydrolyzed polymaleic anhydride, polyaspartic acid and deionized water to prepare a highly efficient and environmentally friendly phosphate-free water dispersant.
[0031] The present invention has the following beneficial effects:
[0032] 1. Lignin, as a natural polymer scale inhibitor, contains many hydroxyl groups and has a certain inhibitory effect on the growth of salt scale crystals such as Ca and Mg; however, natural high molecular polymers are not stable in composition and performance, and are easily decomposed under high temperature and high pressure. The present invention first uses a coupling agent 3-chloropropyltriethoxysilane to graft with lignin to obtain chlorinated lignin. The silicon element contained in the chlorinated lignin improves its own flame retardant properties; the chlorinated lignin reacts with N,N-diethylallylamine, and the amine group in N,N-diethylallylamine is replaced by the chloride ion in the chlorinated lignin, thereby preparing modified lignin. On the one hand, the stability of the modified lignin is increased by increasing the molecular weight and the number of short alkane chains; on the other hand, the amine functional group can usually react chemically with heavy metal ions to adsorb heavy metal ions and improve the scale inhibition rate of lignin itself.
[0033] The lignin modified by N,N-diethylallylamine contains double bond functional groups, which can be copolymerized with monomethyl fumarate and sodium styrene sulfonate to obtain a high molecular weight modified copolymer; sodium styrene sulfonate has a sulfonic acid group, which can strongly replace metal ions such as calcium and magnesium; the present invention designs a block copolymer and adds the antibacterial substance monomethyl fumarate to the prepared modified copolymer dispersed scale inhibitor, thereby playing an antibacterial and disinfecting role on gray water.
[0034] 2. Glycidyl methacrylate and styrene are polymerized by miniemulsion method to obtain polymer microspheres. The polymer microspheres prepared by miniemulsion polymerization method have the advantages of high system stability and easy control of product particle size. The polymer microspheres prepared by the present invention have the characteristics of small particle size and large specific surface area, thereby improving their own scale inhibition rate; the modified composite microspheres are obtained by copolymerizing glycidyl methacrylate and styrene monomers in a certain proportion; by increasing the proportion of glycidyl methacrylate monomer in the preparation of microspheres, more reactive epoxy groups are introduced into the microspheres; by using the reactive epoxy groups, sodium aminosulfonate and dopamine are introduced into the modified composite microspheres, further enriching the number of sulfonate and hydroxyl functional groups on the modified composite microspheres, and improving the adsorption performance of the prepared modified composite microspheres. In addition, dopamine itself can be deposited on the surface of almost any substance to form a polydopamine film; dopamine deposited on the surface of the above-mentioned microspheres can form a coating effect, thereby obtaining modified composite microspheres composed of multiple layers of adsorbents from the inside to the outside, thereby improving its own scale inhibition efficiency and sustainability. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment provides a method for preparing a modified copolymer for an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0038] A1. Add 50 mL of toluene, 6 g of lignin and 10 mL of 3-chloropropyltriethoxysilane to a 100 mL round-bottom flask, mix and stir at 100 r / min for 10 min to obtain a mixed solid-liquid mixture; then reflux the mixed solid-liquid mixture at 70 ° C for 24 h, and naturally cool to room temperature after the reaction is completed to obtain a reactant. Centrifuge the reactant at 1000 r / min for 30 min, separate the solid and liquid, and obtain chlorinated lignin; wash the chlorinated lignin with ethyl acetate until neutral, and then place it in an oven at 50 ° C to dry to constant weight to obtain chlorinated lignin.
[0039] A2. Place 15g of chlorinated lignin in a 100mL round-bottom flask, then add 20g of N,N-diethylallylamine, heat to 100℃ and reflux for 3h; after the reaction is completed, cool to room temperature. Centrifuge at 1000r / min for 15min, then perform solid-liquid separation and collect the solid. Wash the solid with ethyl acetate until it is neutral, then place it in an oven and dry it at 50℃ to constant weight to obtain modified lignin.
[0040] A3. According to the weight percentage, 10g of sodium hypophosphite, 10g of ammonium superphosphate and 50mL of deionized water were mixed, stirred and dissolved to prepare an initiator solution. A 250mL four-necked flask was connected to a stirrer, a reflux condenser, a thermometer and a dropping funnel; 10g of monomethyl fumarate, 50g of sodium styrene sulfonate and 10g of modified lignin were added to the four-necked flask, mixed and stirred at 100r / min for 5min to obtain a mixed solid-liquid. The four-necked flask was transferred to a water bath, and the temperature of the water bath was set to 100℃; then the above-mentioned initiator solution was added dropwise to the four-necked flask through a separatory funnel, and mechanically stirred at 100r / min for 2h to obtain a modified copolymer.
[0041] Example 2
[0042] This embodiment provides a method for preparing a modified copolymer for an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0043] A1. Add 50 mL of toluene, 6 g of lignin and 12 mL of 3-chloropropyltriethoxysilane to a 100 mL round-bottom flask, mix and stir at 100 r / min for 15 min to obtain a mixed solid-liquid mixture; then reflux the mixed solid-liquid mixture at 65 ° C for 24 h, and naturally cool to room temperature after the reaction is completed to obtain a reactant. Centrifuge the reactant at 1000 r / min for 30 min, separate the solid and liquid, and obtain chlorinated lignin; wash the chlorinated lignin with ethyl acetate until neutral, and then place it in an oven at 55 ° C to dry to constant weight to obtain chlorinated lignin.
[0044] A2. Place 18g of chlorinated lignin in a 100mL round-bottom flask, then add 25g of N,N-diethylallylamine, heat to 105℃ and reflux for 4h; after the reaction is completed, cool to room temperature. Centrifuge at 1000r / min for 16min, then perform solid-liquid separation and collect the solid. Wash the solid with ethyl acetate until it is neutral, then place it in an oven and dry it at 55℃ to constant weight to obtain modified lignin.
[0045] A3. According to the weight ratio, 10g of sodium hypophosphite, 10g of ammonium superphosphate and 50mL of deionized water were mixed, stirred and dissolved to prepare an initiator solution. A 250mL four-necked flask was connected to a stirrer, a reflux condenser, a thermometer and a dropping funnel; 10g of monomethyl fumarate and 50g of sodium styrene sulfonate were added to the four-necked flask, and the four-necked flask was transferred to a water bath, and the temperature of the water bath was set to 105°C; then 15g of modified lignin and the above-mentioned initiator solution were added dropwise to the four-necked flask through a separatory funnel, and mechanically stirred at 100r / min for 2h to obtain a modified copolymer.
[0046] Example 3
[0047] This embodiment provides a method for preparing a modified copolymer for an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0048] A1. Add 50 mL of toluene, 6 g of lignin and 15 mL of 3-chloropropyltriethoxysilane to a 100 mL round-bottom flask, mix and stir at 100 r / min for 10-20 min to obtain a mixed solid-liquid mixture; then reflux the mixed solid-liquid mixture at 70 ° C for 24 h, and naturally cool to room temperature after the reaction is completed to obtain a reactant. Centrifuge the reactant at 1000 r / min for 30 min, separate the solid and liquid, and obtain chlorinated lignin; wash the chlorinated lignin with ethyl acetate until neutral, and then place it in an oven at 60 ° C to dry to constant weight to obtain chlorinated lignin.
[0049] A2. Place 20g of chlorinated lignin in a 100mL round-bottom flask, then add 30g of N,N-diethylallylamine, heat to 110℃ and reflux for 5h; after the reaction is completed, cool to room temperature. Centrifuge at 1000r / min for 20min, then perform solid-liquid separation and collect the solid. Wash the solid with ethyl acetate until it is neutral, then place it in an oven and dry it at 60℃ to constant weight to obtain modified lignin.
[0050] A3. According to the weight ratio, 10g of sodium hypophosphite, 10g of ammonium superphosphate and 50mL of deionized water were mixed, stirred and dissolved to prepare an initiator solution. A 250mL four-necked flask was connected to a stirrer, a reflux condenser, a thermometer and a dropping funnel; 10g of monomethyl fumarate and 50g of sodium styrene sulfonate were added to the four-necked flask, and the four-necked flask was transferred to a water bath, and the temperature of the water bath was set to 110°C; then 20g of modified lignin and the above-mentioned initiator solution were added dropwise to the four-necked flask through a separatory funnel, and mechanically stirred at 100r / min for 2h to obtain a modified copolymer.
[0051] Example 4
[0052] This embodiment provides a method for preparing modified composite microspheres for an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0053] B1. Add 0.5g of initiator methyl persulfate, 5g of emulsifier Tween 20 and 200mL of deionized water to a 500mL four-necked flask, and stir at 100r / min for 10min; then add 10g of styrene to the four-necked flask, and stir at 100r / min for 30min to obtain a premixed solution. Use a syringe to slowly drop 20g of glycidyl methacrylate into the four-necked flask, heat to 70℃ and react for 6h to obtain an emulsion system.
[0054] B2. Add 15g of sodium aminosulfonate to the emulsion system, mix and stir until completely dissolved; then heat to 80°C, stir mechanically at 100r / min for 15h, and cool to room temperature to obtain a composite liquid. Add 10mL of ethanol to the composite liquid to break the emulsion, centrifuge at 1000r / min for 20min in a high-speed centrifuge to obtain a solid; wash the solid three times with deionized water, and then put it in a vacuum oven at 50°C to dry to constant weight to obtain an intermediate.
[0055] B3. Add 200 mL of buffer solution tris(hydroxymethylaminomethane), 200 mg of dopamine hydrochloride and 200 mg of the intermediate into a 250 mL three-necked flask, and ultrasonicate for 10 min at 20 KHz to obtain a mixed solid-liquid. The mixed solid-liquid was mechanically stirred at 100 r / min for 24 h at room temperature, and the pH value of the mixed solid-liquid was always maintained at 8 during the mechanical stirring process; the mixed solid-liquid was centrifuged to obtain a solid; the solid was washed 3 times with distilled water, and then dried to obtain a modified composite microsphere.
[0056] Example 5
[0057] This embodiment provides a method for preparing modified composite microspheres for an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0058] B1. Add 0.5g of initiator methyl persulfate, 5g of emulsifier Tween 20 and 200mL of deionized water to a 500mL four-necked flask, and stir at 100r / min for 10min; then add 10g of styrene to the four-necked flask, and stir at 100r / min for 50min to obtain a premixed solution. Use a syringe to slowly drop 22g of glycidyl methacrylate into the four-necked flask, heat to 70℃ and react for 7h to obtain an emulsion system.
[0059] B2. Add 16g of sodium aminosulfonate to the emulsion system, mix and stir until completely dissolved; then heat to 90°C, stir mechanically at 100r / min for 18h, and cool to room temperature to obtain a composite liquid. Add 10mL of ethanol to the composite liquid to break the emulsion, centrifuge at 1000r / min for 25min in a high-speed centrifuge to obtain a solid; wash the solid three times with deionized water, and then put it in a vacuum oven at 55°C to dry to constant weight to obtain an intermediate.
[0060] B3. Add 200 mL of buffer solution tris(hydroxymethyl)aminomethane), 250 mg of dopamine hydrochloride and 200 mg of the intermediate into a 250 mL three-necked flask, and ultrasonicate for 15 min at 20 KHz to obtain a mixed solid-liquid. The mixed solid-liquid was mechanically stirred at 100 r / min for 24 h at room temperature, and the pH value of the mixed solid-liquid was always maintained at 8 during the mechanical stirring process; the mixed solid-liquid was centrifuged to obtain a solid; the solid was washed with distilled water for 3-5 times, and then dried to obtain a modified composite microsphere.
[0061] Example 6
[0062] This embodiment provides a method for preparing modified composite microspheres for an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0063] B1. Add 0.5g of initiator methyl persulfate, 5g of emulsifier Tween 20 and 200mL of deionized water to a 500mL four-necked flask, and stir at 100r / min for 10min; then add 10g of styrene to the four-necked flask, and stir at 100r / min for 60min to obtain a premixed solution. Use a syringe to slowly drop 25g of glycidyl methacrylate into the four-necked flask, heat to 70℃ and react for 8h to obtain an emulsion system.
[0064] B2. Add 20g of sodium aminosulfonate to the emulsion system, mix and stir until completely dissolved; then heat to 8100°C, mechanically stir at 100r / min for 20h, and cool to room temperature to obtain a composite liquid. Add 10mL of ethanol to the composite liquid to break the emulsion, centrifuge at 1000r / min for 30min in a high-speed centrifuge to obtain a solid; wash the solid three times with deionized water, and then put it in a vacuum oven at 60°C to dry to constant weight to obtain an intermediate.
[0065] B3. Add 200 mL of buffer solution tris(hydroxymethylaminomethane), 300 mg of dopamine hydrochloride and 200 mg of the intermediate into a 250 mL three-necked flask, and ultrasonicate for 20 min at 20 KHz to obtain a mixed solid-liquid. The mixed solid-liquid was mechanically stirred at 100 r / min for 24 h at room temperature, and the pH value of the mixed solid-liquid was always maintained at 9 during the mechanical stirring process; the mixed solid-liquid was centrifuged to obtain a solid; the solid was washed 5 times with distilled water, and then dried to obtain a modified composite microsphere.
[0066] Example 7
[0067] This embodiment provides a method for preparing an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0068] According to weight parts, 50-60 parts of the modified copolymer prepared in Example 1, 20-30 parts of the modified composite microspheres prepared in Example 4, 10 parts of hydrolyzed polymaleic anhydride, 10 parts of polyaspartic acid and 10 parts of deionized water are added to a reactor, and mixed and stirred at 100 r / min for 30-60 minutes to prepare an efficient and environmentally friendly phosphate-free water dispersant.
[0069] Example 8
[0070] This embodiment provides a method for preparing an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0071] According to weight parts, 50-60 parts of the modified copolymer prepared in Example 2, 20-30 parts of the modified composite microspheres prepared in Example 5, 10 parts of hydrolyzed polymaleic anhydride, 10 parts of polyaspartic acid and 10 parts of deionized water are added to a reactor, and mixed and stirred at 100 r / min for 30-60 minutes to prepare an efficient and environmentally friendly phosphate-free water dispersant.
[0072] Example 9
[0073] This embodiment provides a method for preparing an efficient and environmentally friendly phosphorus-free water dispersant, comprising the following steps:
[0074] According to weight parts, 50-60 parts of the modified copolymer prepared in Example 3, 20-30 parts of the modified composite microspheres prepared in Example 6, 10 parts of hydrolyzed polymaleic anhydride, 10 parts of polyaspartic acid and 10 parts of deionized water are added to a reactor, mixed and stirred at 100 r / min for 30-60 min to prepare an efficient and environmentally friendly phosphate-free water dispersant.
[0075] Comparative Example 1
[0076] Compared with Example 9, in this comparative example, when preparing the modified copolymer, no modified lignin was added, and only monomethyl fumarate and sodium styrene sulfonate were copolymerized.
[0077] Comparative Example 2
[0078] Compared with Example 9, in this comparative example, no modified copolymer was added when preparing the high-efficiency and environmentally friendly phosphorus-free water dispersant.
[0079] Comparative Example 3
[0080] Compared with Example 9, in this comparative example, dopamine hydrochloride was not used for modification when preparing the modified composite microspheres.
[0081] Comparative Example 4
[0082] Compared with Example 9, in this comparative example, monomethyl fumarate was not added when preparing the modified copolymer.
[0083] Performance Test:
[0084] 1. The scale inhibition rate of the high-efficiency and environment-friendly phosphate-free water dispersant for calcium carbonate scale prepared in Examples 7-9 and Comparative Examples 1-4 was determined according to the determination method of Q / SHSLJ1452-2002 "General Technical Requirements for Scale Inhibitors for Oilfield Produced Water Treatment".
[0085] 2. The scale inhibitory effect of the highly efficient and environmentally friendly phosphate-free water dispersants prepared in Examples 7-9 and Comparative Examples 1-4 on calcium sulfate was determined according to the determination method of Q / SHSLJ1452-2002 "General Technical Requirements for Scale Inhibitors for Oilfield Produced Water Treatment".
[0086] 3. The MTT method was used to test the minimum inhibitory concentration of Gram-negative bacteria of the high-efficiency and environmentally friendly phosphate-free water dispersants prepared in Examples 7-9 and Comparative Examples 1-4.
[0087] Table 1
[0088]
[0089] Data Analysis:
[0090] Analyzing the data in Table 1, the high-efficiency and environmentally friendly phosphorus-free ash water dispersants prepared in Examples 7-9 of the present invention all have good calcium carbonate scale inhibition rates and calcium sulfate scale inhibition rates; however, since no modified lignin was added in Comparative Example 1 and no modified copolymer was added in Comparative Example 2, the prepared ash water dispersants had low scale removal rates for calcium carbonate and calcium sulfate; when preparing composite microspheres in Comparative Example 3, dopamine hydrochloride was not used for modification, which correspondingly reduced the scale removal rates for calcium carbonate and calcium sulfate.
[0091] The high-efficiency and environmentally friendly phosphorus-free ash water dispersants prepared in Examples 7-9 of the present invention all have good antibacterial effects, which are manifested as having smaller antibacterial concentration values. However, in Comparative Example 4, since monomethyl fumarate was not added when preparing the modified copolymer, the antibacterial properties of the prepared ash water dispersant itself were reduced.
[0092] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0093] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0094] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A highly efficient and environmentally friendly phosphorus-free water dispersant, characterized in that: In parts by weight, it comprises 50-60 parts of a modified copolymer, 20-30 parts of modified composite microspheres, 10 parts of hydrolyzed polymaleic anhydride, 10 parts of polyaspartic acid and 10 parts of deionized water; The preparation method of the modified copolymer comprises the following steps: A1, toluene, lignin and 3-chloropropyltriethoxysilane are mixed and stirred to obtain a mixed solid-liquid; the mixed solid-liquid is refluxed at 70-80° C. for 24 hours, and after the reaction is completed, it is naturally cooled to room temperature to obtain a reactant; the reactant is subjected to a post-treatment process to obtain chlorinated lignin; A2, mixing chlorinated lignin and N,N-diethylallylamine, heating to 100-110°C for reflux reaction for 3-5h; and obtaining modified lignin through post-treatment process; A3. Dissolve sodium hypophosphite, ammonium superphosphate and deionized water to obtain an initiator solution; mix and stir monomethyl fumarate, sodium styrene sulfonate and modified lignin to obtain a mixed solid-liquid; then add the initiator solution drop by drop into the mixed solid-liquid, react at 100-110° C. for 2 hours to obtain a modified copolymer.
2. A highly efficient and environmentally friendly phosphorus-free water dispersant according to claim 1, characterized in that: In step A1, the dosage ratio of toluene, lignin and 3-chloropropyltriethoxysilane is 50mL:6g:10-15mL; the post-treatment process includes: centrifuging the reactants at 1000r / min for 30min and separating to obtain solid chlorinated lignin; washing the chlorinated lignin with ethyl acetate to neutrality, and then drying at 50-60°C to constant weight to obtain chlorinated lignin.
3. A highly efficient and environmentally friendly phosphorus-free water dispersant according to claim 2, characterized in that: In step A2, the usage ratio of chlorinated lignin and N,N-diethylallylamine is 15-20g:20-30g; the post-treatment process includes: centrifuging at 1000r / min for 15-20min, then performing solid-liquid separation, and collecting solids; washing the solids with ethyl acetate to neutrality, and then placing them in an oven at 50-60°C to dry to constant weight to obtain modified lignin.
4. A highly efficient and environmentally friendly phosphorus-free water dispersant according to claim 3, characterized in that: In step A3, the dosage ratio of sodium hypophosphite, ammonium superphosphate and deionized water is 10g:10g:50mL; the dosage ratio of monomethyl fumarate, sodium styrene sulfonate and modified lignin is 10g:50g:10-20g.
5. The high-efficiency and environmentally friendly phosphorus-free water dispersant according to claim 1, characterized in that: The preparation method of the modified composite microspheres comprises the following steps: B1, initiator, emulsifier and deionized water are mixed evenly, and then styrene is added, mixed and stirred to obtain a premixed solution; glycidyl methacrylate is then added dropwise to the premixed solution, and the temperature is raised to 70°C for reaction for 6-8h to obtain an emulsion system; B2, add sodium aminosulfonate to the emulsion system, mix and stir until completely dissolved; then heat to 80-100°C for reaction for 15-20h, cool to room temperature to obtain a composite liquid; add ethanol to the composite liquid to demulsify, centrifuge to obtain a solid; wash the solid with deionized water, dry at 50-60°C to constant weight, and obtain an intermediate; B3, tris(hydroxymethyl)aminomethane, dopamine hydrochloride and the intermediate are ultrasonically mixed to obtain a mixed solid-liquid; the mixed solid-liquid is post-treated to obtain modified composite microspheres.
6. A highly efficient and environmentally friendly phosphorus-free water dispersant according to claim 5, characterized in that: In step B1, the initiator is methyl persulfate and the emulsifier is Tween 20; the dosage ratio of the initiator, the emulsifier and deionized water is 0.5g:5g:200mL; the mixing speed is 100r / min and the mixing time is 30-60min; the dosage ratio of styrene and glycidyl methacrylate is 10g:20-25g.
7. A highly efficient and environmentally friendly phosphorus-free water dispersant according to claim 6, characterized in that: In step B2, the amount of sodium sulfamate is 15-20g, and the amount of ethanol is 10mL; the centrifugal speed is 1000r / min, and the centrifugal time is 20-30min; in step B3, the amount ratio of tris(hydroxymethyl)aminomethane, dopamine hydrochloride and the intermediate is 200mL:200-300mg:200mg; the ultrasonic frequency is 20KHz, and the ultrasonic time is 10-20min; the post-treatment includes: reacting the mixed solid and liquid at room temperature for 24h, and maintaining the pH value of the mixed solid and liquid at 8-9 during the reaction; centrifuging the mixed solid and liquid to obtain a solid; washing the solid with distilled water for 3-5 times, and then drying to obtain a modified composite microsphere.
8. A method for preparing a highly efficient and environmentally friendly phosphorus-free water dispersant according to any one of claims 1 to 7, characterized in that: The preparation method of the high-efficiency and environment-friendly phosphorus-free water dispersant is as follows: the modified copolymer, the modified composite microspheres, the hydrolyzed polymaleic anhydride, the polyaspartic acid and the deionized water are uniformly mixed to prepare the high-efficiency and environment-friendly phosphorus-free water dispersant.
Citation Information
Patent Citations
Phosphorus-free green environment-friendly grey water dispersing agent resistant to low-temperature storage
CN115477398A
Treating agent for heavy metal waste water and preparation method and application thereof
CN106430647A
Treatment of boiler water
JP1994108274A